KORELASI ANTARA KEDALAMAN SEDIMEN DI PELABUHAN BENOA DAN KONSENTRASI LOGAM BERAT Pb DAN Cu - Siaka, I M. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 2 Juli 2008)
An investigation on the correlation between the depth of sediment in Benoa estuary and the concentration of Pb and Cu. Statistically, the sample collecting location and the sediment depth influenced the concentration of lead (Pb) and copper (Cu) significantly. The variation resources of interaction between sample collecting location and the sediment depth also showed a great influence. In general, the deeper the sediments, the lower the concentration of Pb and Cu are. The average concentrations of heavy metals found in surface layer (0 cm) were 15.52 mg/kg of Pb and 35.85 mg/kg of Cu. Sediment in the depth of 10 cm contained 13.49 mg/kg of Pb and 33.69 mg/kg of Cu, while the sediment in the depth of 20 cm contained 11.51 mg/kg of Pb and 32.22 mg/kg of Cu.
Keywords: correlation, sediment, depth, heavy metals